The Effect of Profitability, Solvency and Company Size On Audit Delay - Vina Citra Mulyandani; Yattaqi Qintha (Publikasi Indonesia, 2022)
This study aims to determine the effect of profitability, solvency and company size on audit delay in manufacturing companies listed in Indonesia Stock Exchange periode 2015-2019. Profitability measures using Return On Asset, solvency using Debt to Asset Ratio and company size using the natural logarithm of Total Asset. This type of research is quantitative research with secondary data, namely audited annual financial report and independent auditor reports from manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique used purposive sampling, with a sample of 40 companies. The data analysis technique used multiple linear regression analysis. The results of this study partially show that profitability and solvency have significant effect on audit delay, while firm size has no significant effect on audit delay. The results of this study simultaneously show that profitability, solvency, and firm size have a significant effect on audit delay.